Neoadjuvant Platinum Based Chemotherapy in Triple Negative Breast Cancer-Preliminary Experience from A Tertiary Cancer Centre. - Praveen Kumar Shenoy; Joneetha Jones; Vinin N V; Manuprasad A; Geetha M; Priya Rathi (International Journal of Pharma and Bio Sciences, 2021)
Triple negative breast cancers are found to have poor prognosis. It has been postulated that pathological complete response (pCR) to neoadjuvant chemotherapy can be a surrogate for survival in TNBC. Various combinations of chemotherapeutic agents have been tried to improve the pCR rates including addition of platinum compounds. Although western data is available no studies till date have reported this from a developing world. This study intends to find out the pCR rates and the disease free survival and the overall survival for patients treated with neoadjuvant chemotherapy (NACT) with paclitaxel and carboplatin in locally advanced TNBC. The study was conducted at a rural tertiary cancer centre in South India. This was a retrospective analysis of medical records of patients who underwent NACT with paclitaxel and carboplatin from 1st January 2014 to 31st December 2018 at. Malabar Cancer Centre. A total of 33 patients underwent chemotherapy with paclitaxel and carboplatin during the study period. The median age was 51 years. 59% of patients had stage IIIA disease.96% of patients took all 12 cycles of NACT. 43% of patients had complete response to neo adjuvant chemotherapy whereas 57% of patients had partial response to chemotherapy. This was comparable to the available literature. The four year disease free survival was 81% and the four year overall survival was 86% in this study. No statistically significant difference in survival could be found in those patients who achieved pCR when compared to those who did not. Studies with a larger number of patients are needed to throw light in this aspect.